NeMO–AD, a new neuroscience multi‐omic visualization and analysis platform for Alzheimer's disease research. (December 2021) - Chrysostomou, Elena; McDaniel, Kennedy E; Prater, Katherine E; Casas, Brandon A; Song, Yang; Orvis, Joshua; Kancherla, Jayaram; Herb, Brian; Bravo, Hector C; Mahurkar, Anup A; White, Owen; Ament, Seth; et al.
Abstract: Background: Recent years have resulted in tremendous progress in understanding Alzheimer's disease (AD) via the generation and analysis of multi‐omic data. In addition, the BRAIN initiative has been mapping gene expression in the normal brain. However, a barrier for the broad usage of these data has been limited access and the requirement for informatics support to allow biologists to meaningfully access this wealth of information. To address this challenge, we extended the Neuroscience Multi‐Omic (NeMO) Analytics (nemoanalytics.org) platform to include a focus on Alzheimer's disease ("NeMO‐AD"). Method: NeMO Analytics gene expression tools are powered by gEAR (umgear.org) and consist of six components: (i) An expression browser, for visualization of gene expression across multiple datasets; (ii) A dataset compare tool for comparing all the genes between two groups; (iii) An elaborate single cell workbench; (iv) A dataset uploader that allows the user to upload their own multi‐omic data; (v) A dataset curator that allows the user to define visualization preferences (e.g., data presentation as bar, line, x‐y scatter, violin plot, tSNE, or SVG); and (vi) A dataset manager, which allows you to organize datasets into profiles and manage privacy and dataset sharing. NeMO Analytics also allows the visualization of epigenetic data via integration of the Epiviz tool (https://epiviz.github.io/). Result: Currently, NeMO‐AD consists of 32 impactful AD datasets, including bulk RNA‐seq (40.6%), microarray (43.8), single‐cell RNA‐seq (12.5%) and single‐nuclei RNA‐seq (3.1%) from both human (40.6%) and mouse models (59.4%). The datasets have been organized into 8 different "profiles" (collections of similarly themed datasets, allowing for side‐by‐side visualization): specific brain regions, experimental models of AD, microglia, therapeutic targets, AD progression, molecular brain aging, biomarkers and other. Users can create their own profiles and upload their own datasets which can be made public, private or shared with collaborator(s). Conclusion: NeMO‐AD offers biologists access to impactful multi‐omic data relevant to Alzheimer's disease that can be explored without assistance from bioinformaticians. The broad usage of this platform to share and disseminate data could result in a more rapid progression of AD research.